Developing forest-based bioeconomy in the Region of North Karelia, Finland : Opportunities in co-operation with China - den Herder, Michael; Wallius, Venla; Konu, Henna; Heräjärvi, Henrik; Viitanen, Jari; Mutanen, Antti; Kurttila, Mikko; Chen, Xiaoqian (Natural Resources Institute Finland (Luke), 2022)
The region of North Karelia, Finland, has a strong forest-based bioeconomy sector. This report describes the region’s opportunities for increasing co-operation in forest-based bioeconomy with China. The forest-based bioeconomy sectors covered in this report include wood products, non-wood forest products (NWFPs), and nature-based tourism (NBT). Moreover, this report presents two future scenarios for bioeconomy development in North Karelia. The results indicate that there are untapped potentials in North Karelian forest-based bioeconomy to grow with increasing co-operation with China. New value-adding products and services may be identified to meet the needs of Chinese consumers and business collaborators. For wood-based products, the new possibilities mostly relate to re-organizing the export product structure from primary products towards further processed ones, as well as incorporating services with the export products. For NWFPs, export potentials were identified in North Karelian chaga and reishi mushroom products and further processed goods. In terms of NBT sector, North Karelia can offer unique, sustainable, and high-quality NBT experiences for Chinese niche markets. This includes professional and educational tourism. North Karelian companies should re-organise and tighten their internal networks and enhance co-operation by integrating different sectors to meet the demand, to develop new products and services, and to carry out joint marketing in China. Finnish sauna, an esteemed Finnish brand with a rapidly increasing market demand in China, was identified as a concept worth further developing in North Karelia. Our desired scenario suggests that growing businesses would bring hundreds of new jobs and hundreds of millions of euros turnover in North Karelia annually. However, several barriers need to be overcome. Current products with low production volumes are suitable to niche markets, but identifying these markets, creating and fostering the mandatory contacts, and establishing viable business requires long-term and systematic work. North Karelia has huge capacity in forest-based circular bioeconomy. Systematic branding can transform North Karelia into an international knowledge hub for businesses and academia related to different forest bioeconomy sectors. This will not only have beneficial impacts on the regional economy in North Karelia but also far-reaching impacts on the global sustainability of the bioeconomy sector. North Karelian forest-based bioeconomy expertise can still increase its global footprint in improving the sustainable use of natural resources.
Keywords: bioeconomy; forest-based bioeconomy; wood products; non-wood forest products; forest products; nature-based tourism; North Karelia; China